Promoting ecological citizenship at the university level - Arbues, Elena; Celaya, Inaki; Naval, Concepcion (Frontiers in Education, 2025)
This review article analyses the role of the university in the promotion of ecological civic responsibility as an educational response to the global challenges of sustainability due to the present-day environmental crisis. By means of a documentary review of the main international conferences, regulatory frameworks and scientific literature on environmental education and sustainable development, it examines the policies and practices to be implemented in the university area. The results show growth in the integration of sustainability in academic programs and in models for sustainable campuses. It proposes various innovative pedagogical methodologies such as blended learning, character education, service-learning, and some of the emerging digital media like podcasting which promote ethical, critical and participatory learning. And it concludes that higher education must accept an active cross-disciplinary and interdisciplinary commitment to sustainability, thereby producing citizens capable of leading social and environmental transformations from the perspective of the ethics of care, responsibility and democratic participation.